2006
DOI: 10.1037/0022-3514.90.6.999
|View full text |Cite
|
Sign up to set email alerts
|

The mismatch effect: When testosterone and status are at odds.

Abstract: Why do some people strive for high status, whereas others actively avoid it? In the present studies, the authors examined the psychological and physiological consequences of a mismatch between baseline testosterone and a person's current level of status. The authors tested this mismatch effect by placing high and low testosterone individuals into high or low status positions using a rigged competition. In Study 1, low testosterone participants reported greater emotional arousal, focused more on their status, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
195
4
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(235 citation statements)
references
References 58 publications
(95 reference statements)
32
195
4
4
Order By: Relevance
“…Second, status and hierarchical stability interactively influenced testosterone reactivity, which negatively predicted interview performance. This biological pathway extends prior research, in which higher basal testosterone levels were related to status-seeking motivation and impaired cognitive performance under conditions of experimentally induced status threat (e.g., defeat in competition) (26)(27)(28). Elevated testosterone reactivity in the present study may have led individuals to focus on their threatened status, rather than the speech task at hand, disrupting cognitive functioning when delivering the speech, and undermining performance evaluations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Second, status and hierarchical stability interactively influenced testosterone reactivity, which negatively predicted interview performance. This biological pathway extends prior research, in which higher basal testosterone levels were related to status-seeking motivation and impaired cognitive performance under conditions of experimentally induced status threat (e.g., defeat in competition) (26)(27)(28). Elevated testosterone reactivity in the present study may have led individuals to focus on their threatened status, rather than the speech task at hand, disrupting cognitive functioning when delivering the speech, and undermining performance evaluations.…”
Section: Discussionsupporting
confidence: 80%
“…Prior research on acute cortisol responses and performance outcomes in stressful contexts has yielded mixed results (e.g., decision making performance) (23)(24)(25), but the consequences of acute testosterone responses for performance under social-evaluative stress have been largely overlooked. There is indirect evidence that elevated basal testosterone concentrations in status-threatening situations (e.g., losing a competition) predicts hypervigilance to status cues and impaired cognitive performance (26)(27)(28). Extending this prior research to the present study, we explored whether acute cortisol or testosterone responses to the stressor explained the effects of status and hierarchy instability on social-evaluative performance.…”
Section: Significancementioning
confidence: 85%
“…Finally, others have shown that testosterone administration in females (17) seems to increase status-seeking behavior, and this finding agrees with correlations between endogenous testosterone levels and status-related behaviors shown in men (for a review, see ref. 18) and women (44)(45)(46)(47). This research adds to the growing evidence that testosterone plays an important role in female social behavior (48)(49)(50)(51).…”
Section: Methodsmentioning
confidence: 65%
“…According to the literature, these are the individuals who should benefit most from gains in power and status (Josephs et al, 2006;Mehta, Wuehrmann, & Josephs, 2009;Zyphur et al, 2009) and thus should experience the greatest reduction in stress.…”
Section: Resultsmentioning
confidence: 99%